Apakah Menikah Menyebabkan Partisipasi Kerja Perempuan di Bali Lebih Banyak Terlibat dalam Sektor Informal? - Ni Putu Meitha Setiawati; I Gusti Agung Ayu Apsari Anandari; I Wayan Sukadana (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2025)
Bali Province in 2023 recorded the highest female unemployment rate in all of Indonesia, but these women tend to work in the informal sector rather than the formal sector, even though jobs in the informal sector have high work risks, no social security, minimal protection, and low wages. Using data from the National Labor Force Survey (Sakernas) in August 2023, this study aims to analyze the participation of married women in the decision to work in the informal sector in Bali Province with control variables of education level, age, area of residence, and training participation. Analysis with binary logistics shows that married women tend to work in the informal sector, assuming that factors other than those under study are considered to remain constant. Further analysis discussed the outpouring of working hours of women workers in Bali Province using the Tobit regression model. The results show that married women have significantly higher working hours. The high tendency of women to marry and their tendency to work in the informal sector with significant working hours, requires comprehensive intervention to ensure the welfare of Balinese women who work in sectors that are classified as less secure.